PENGARUH PENILAIAN PRESTASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA DI BAGIAN LINE NEW ISIS PADA PT. SUMITOMO BATAM INDONESIA - Tulus Manurung; Ferry Muliadi Manalu; Dini Anggraini (University of Riau Kepulauan, 2016)
The purpose of this study was to determine whether is a positive and significant relationship between performance appraisal and leadership style on work productivity, as well to determine jointly whether is a positive and significant relationship between job performance and assessment of leadership style on produktivity at work PT. Sumitomo Batam Indonesia. From the result of multiple regresion analysis, the equation obtained to predict the magnitude of the effect between the independent variable (X) of the variable is dependent (Y), namely produktivity (Y)=2.664+2.450X1+1.184X2. cab be seen that the assessment of work performance/achievement has more higre influence than the leadership style. Of the F-test result, obtained valuaes of 49.196, F value with probality values (sig) = 0,000. Fcount ( 49.196) Ftable (3,09), and the sig smaller than the probality value of 0,05 or 0,000 0,05; Means jointly work performance appraisal and leadership style have a significant effect on labor produktivity. From the result of the t-test, in can be concluded that the variable job performance appraisal and leadership style variable has a significant influence on labor produktivity, with a significant level of 0,05% or 5%. Calculation ofthe t-test showed that the tcount ttable.